'Drone-Netting' for Sampling Live Insects. Issue 5 (11th September 2020) - Löcken, Helge; Fischer, Ottmar W; Selz, Jürgen; Boppré, Michael
Abstract: Drones have become valuable tools for biodiversity studies by providing aerial photographs; however, for most entomological studies, images, in particular those taken remotely, are usually insufficient; rather sampling of specimens is required. We equipped a cheap off-the-shelf drone with a net bag, flew it over the ground, sweeping the vegetation, and sampled adult and larval insects as well as spiders. 'Drone-netting' proved to be a versatile method for general insect sampling, particularly in inaccessible terrains. It is time- and cost-effective, minimally invasive, and adaptable for many research tasks in entomofaunistics; it shows a degree of representativeness similar to hand-netting, and caught specimens stay alive and can be released if not needed.